Avaliação do potencial leishmanicida de derivados guanilidrazônicos e tiossemicarbazônicos - Santos, Mariana da Silva (2015)
Leishmaniasis is among the world's five highest parasitic diseases and according to the World Health Organization (WHO), affects more than 12 million people around the world and is expected to be around two million new cases each year. Although a serious public health problem, to date there is no ideal treatment, considering that the available drugs have serious adverse effects, such as the pentavalent antimonials, drugs of choice for the treatment, which is one of the main side effects cardiotoxicity. Therefore, this work had as main objective the evaluation of leishmanicidal activity guanylhydrazones and thiosemicarbazones derivatives in search of new prototypes of antileishmanial drugs to submit less toxic and more effective than those available in the pharmaceutical market. For this, we investigated the leishmanicidal potential of the twenty guanylhydrazones derivatives and three thiosemicarbazones derivatives. It was observed, that derivatives of the twenty guanylhydrazones, only four showed no cytotoxicity for the J774 macrophage lineage, up to the maximum concentration tested (100 μM): LQM 3, LQM 4, LQM 11 e LQM 16; and the three thiosemicarbazones derivatives, only thiosemicarbazone derivative LQM 17(1) did not show deleterious effect on the cells until the concentration of 100 uM. It was also seen that some derivatives showed potent activity against Leishmania chagasi promastigotes highlighting guanylhydrazones derivatives LQM 5, LQM 8, LQM 10, LQM 14 e LQM 17, and the tree thiosemicarbazones derivatives LQM 10(1), LQM 14(1) e LQM 17(1) that showed IC50 below 10 μM and maximal effect above the 90%. Moreover, the guanylhydrazone derivative LQM 19 and thiosemicarbazone derivative LQM 17(1) were the only ones showed activity against amastigotes of Leishmania chagasi, above 60%. Being the LQM 17(1) derivative selected for the realization of scanning electron microscopy (SEM) and also for the in vivo test with Mesocricetus auratus (Golden Hamster). It was observed that the LQM 17(1) derivative showed effect on the course of infection in spleen of Mesocricetus auratus infected with Leishmania chagasi (100 μmol/kg/dia/15 dias (i.p.)) without altering liver enzymes (AST and ALT), and creatinine and urea, renal metabolites, the derivative did not cause significant changes in the parameters for evaluation of liver and kidney toxicity. Still being seen, that it was able to alter the spleen size statistically significant way, which could be indicative of immunostimulatory substance or toxicity. Thus this study demonstrated that thiosemicarbazone derivative LQM 17(1) showed a leishmanicidal potential against Leishmania chagasi, and could be used as a prototype for the development of new antileishmanial drugs.